2021
DOI: 10.1016/j.jds.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-observer agreements in detecting peri-implant bone defects between periapical radiography and cone beam computed tomography: A clinical study

Abstract: Background/purpose Information regarding agreements between periapical radiograph (PA) and cone beam computed tomography (CBCT) in detecting peri-implant defect is still scarce. The aim of this clinical study was to compare agreements between PA and CBCT in detecting peri-implant bone defect. Materials and methods This retrospective clinical study enrolled 32 patients with both PA and CBCT filmed right after implant placement. Four modalities were used for film reading:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Schriber et al, 2020, found that DMFR observers reported a more accurate performance than OMFS (oral and maxillofacial surgeons) in the diagnosis of peri‐implant bone defects using CBCT. Zhang et al, 2021 found that agreement between experienced dentists (5 years of experience in implant imaging) was higher than that of inexperienced observers in the detection of peri‐implant defects by CBCT and periapical radiographs. This is in accordance with the present study, in which, DMFR showed a higher agreement with the correct diagnosis, which can be attributed to their higher degree of experience and training for this task.…”
Section: Discussionmentioning
confidence: 99%
“…Schriber et al, 2020, found that DMFR observers reported a more accurate performance than OMFS (oral and maxillofacial surgeons) in the diagnosis of peri‐implant bone defects using CBCT. Zhang et al, 2021 found that agreement between experienced dentists (5 years of experience in implant imaging) was higher than that of inexperienced observers in the detection of peri‐implant defects by CBCT and periapical radiographs. This is in accordance with the present study, in which, DMFR showed a higher agreement with the correct diagnosis, which can be attributed to their higher degree of experience and training for this task.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of density analysis and bone morphometry for each periapical radiograph were performed by an intraobserver test. The observers repeated the evaluation three times in a 2-week interval [ 36 ]. The morphometric measurement started with converting all the data from DICOM to 64-bit format and then determining the region of interest (ROI) using the free-hand selection tool.…”
Section: Methodsmentioning
confidence: 99%
“…Further information regarding the reproducibility of the PD [33][34][35][36][37][38][39][40][41] and BoP 26 measurement as well as the agreement in bone level assessment on intraoral radiographs [42][43][44][45] is available as Supplementary Material S3 in the online Journal of Periodontology.…”
Section: Supplementary Factors Affecting Reproducibility Of Peri-impl...mentioning
confidence: 99%